The Association Between Periodontal Disease and Pregnancy Loss: A Systematic Review and Meta-Analysis - Kashefi baher, Mohammadreza (Journal of Dental School, 2025)
Objective(s): Periodontal pathologies, specifically gingivitis and periodontitis, are posited to exert influence on systemic health states, encompassing pregnancy outcomes. While prior investigations have explored the relationship between periodontal disease and adverse pregnancy outcomes (APOs), including premature birth, low birth weight, and preterm low birth weight, as well as preeclampsia, the correlation with pregnancy termination remains equivocal. The present systematic review and meta-analysis aimed to elucidate the potential association between periodontal disease and diverse manifestations of pregnancy loss. Methods: A thorough review of the literature was performed using PubMed, Scopus, Web of Science, and Google Scholar identified studies on the link between periodontal disease and pregnancy loss, focusing on those meeting criteria that documented the disease in pregnant women and its association with pregnancy loss. To quantitatively synthesize the existing evidence, meta-analytic techniques utilizing Stata/MP 17.0 software were employed. The strength of the relationships between variables was determined through the computation of odds ratios (OR) and their corresponding 95% confidence intervals (CI). Results: A review of 649 studies identified 14 for qualitative synthesis and 5 for meta-analysis. Qualitative findings on the link between periodontal disease and pregnancy loss were inconsistent, with some studies showing a significant association, while others did not. The ORs also exhibited substantial heterogeneity. Additionally, a limited number of studies suggested a potential, albeit marginally significant, inverse correlation between periodontal treatment and pregnancy loss. A meta-analysis of cohort studies found a significant link between periodontal disease and higher pregnancy loss risk (OR = 2.878, 95% CI: 1.158–4.599), while case-control studies showed no significant association (OR = 2.459, 95% CI: 0.270–4.648). Conclusion: Considering the modifiable nature of periodontal disease, the incorporation of dental interventions within preconception and antenatal healthcare protocols may serve as a strategy to mitigate pregnancy loss risk.